Development, validation of liquid chromatography-tandem mass spectrometry method for simultaneous determination of rosuvastatin and metformin in human plasma and its application to a pharmacokinetic study - P Pavan Kumar; T. E. G. K. Murthy; M V Basaveswara Rao (Wolters Kluwer Medknow Publications, 2015)
A new, simple and accurate liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for simultaneous determination of rosuvastatin (ROS) and metformin (MET) in human plasma was developed. The assay procedure involved simple protein precipitation with acetonitrile. Following precipitation, fraction of supernatant was decanted and evaporated under gentle stream of nitrogen at 40΀C. The residue was reconstituted in mobile phase and injected. The chromatographic separation was achieved with Thermo Hypurity C18 column (50 mm Χ 4.6 mm, 5 μ) using a mobile phase composition containing 0.1% v/v formic acid in water and acetonitrile (30:70, v/v) at a flow rate of 0.4 mL/min. The total run time was 3.5 min. The method showed good linearity in the range 0.5-200 ng/mL for ROS and 2-2000 ng/mL for MET with correlation coefficient (r) >0.9994 for both the analytes. The intra and inter-day precision values for ROS and MET met the acceptance criteria as per regulatory guidelines. The battery of stability studies viz., bench-top, freeze-thaw and long term stability were performed. The developed method was applied to a pharmacokinetic study.